Speeding up adiabatic population transfer in a Josephson qutrit via counter-diabatic driving. (8th December 2017) - Feng, Zhi-Bo; Lu, Xiao-Jing; Li, M; Yan, Run-Ying; Zhou, Yun-Qing
Abstract: We propose a theoretical scheme to speed up adiabatic population transfer in a Josephson artificial qutrit by transitionless quantum driving. At a magic working point, an effective three-level subsystem can be chosen to constitute our qutrit. With Stokes and pump driving, adiabatic population transfer can be achieved in the qutrit by means of stimulated Raman adiabatic passage. Assisted by a counter-diabatic driving, the adiabatic population transfer can be sped up drastically with accessible parameters. Moreover, the accelerated operation is flexibly reversible and highly robust against decoherence effects. Thanks to these distinctive advantages, the present protocol could offer a promising avenue for optimal coherent operations in Josephson quantum circuits.